2000
DOI: 10.1002/(sici)1099-0488(20000315)38:6<874::aid-polb7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and rheology of hyperbranched and dendritic polymers. II. Effects of blending acetylated and hydroxy-terminated poly(propyleneimine) dendrimers with aqueous poly(ethylene oxide) solutions

Abstract: The effect of adding acetylated poly(propyleneimine) dendrimers to the structure and rheology of aqueous solutions of high molecular weight poly(ethylene oxide) (PEO) was investigated by rheology and small‐angle neutron scattering in a temperature range of 10–40 °C. In the semidilute regime, the steady shear rheology of PEO solutions was unmodified by the addition of dendrimers at a comparable weight concentration. At the highest concentrations studied, the addition of acetylated dendrimers suppressed the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The novel rheological and structural properties of these dendrimer solutions points toward their application as rheology modifiers. In the next contribution,33 we explore the effects of solution‐blending these dendrimers with linear, flexible, water‐soluble polymers on the rheology and molecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…The novel rheological and structural properties of these dendrimer solutions points toward their application as rheology modifiers. In the next contribution,33 we explore the effects of solution‐blending these dendrimers with linear, flexible, water‐soluble polymers on the rheology and molecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that dendritic polyether and poly͑amidoamine͒ melts exhibit a Newtonian behavior over the available measurement range in experiments and the lack of entanglements in the systems observed suggests that as the dendritic topology leads to globular conformations, molecules do not interpenetrate significantly in the melt and do not combine to form aggregated structures. 4 In the case of dendritic polymers in solution, a peak is observed in the plot of intrinsic viscosity versus molecular mass. 5 This is in contrast with linear chains which obey the Mark-Houwink equation 6 and show a steady increase in the intrinsic viscosity as a function of molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these earlier studies, our work focuses on determining the influence of the chemical nature of the molecular end groups on the conformation and rheology of dendrimers. Previous work with acetylated PPI dendrimers focuses on solution structure, rheology, and interactions with linear polymers in water. , In this work, we have examined both the solution architecture and melt rheology of fourth- and fifth-generation poly(propyleneimine) (PPI) dendrimers derivatized with two different acrylate monomers. The results of density measurements along with steady and dynamic rheology are analyzed to draw connections between copolymer composition, molecular structure, and bulk mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%